OPTIMALIZATION TEENAGERS THROUGH THE “GEMAR” SAVINGS CULTURE - Farida, Nur; Qomariah, Siti Nur (SYNTIFIC, 2024)
Background. Smoking behavior is a behavior that is harmful to health and male teenage smokers increase every year in Indonesia. Currently, a consumptive life is commonplace by spending money only on food and having fun which is done excessively so teenagers need to be taught to manage money. Purpose. This community service aimed to reduce teenagers’ smoking behavior by teaching them to enjoy saving called GEMAR (Gerakan Mengurangi Rokok) by saving culture. Activity methods. This community service activity provides education about smoking behavior and financial management to increase knowledge and understanding of teenagers in Kebomas Village regarding financial management by saving, then reducing negative smoking behavior, and helping to develop teenagers' creativity in using used goods into more useful items for saving. Findings. The teenagers are interested and pay good attention to this community service activity. Teenagers' behavior of smoking has changed after this community service activity. After this activity, most teenagers have good knowledge about 10 people (76.9%) and moderate action in smoking 8 people (61.5%). Conclusion. Highlighting the need for better money management. Teenagers in Kebomas Village actively participated in an activity promoting saving activities to reduce smoking and replace positive activities with future savings.